Corporate governance and executive compensation in Chinese e-commerce industry - Dong, Xinyi (2022)
This study examines the correlation between executive compensation and corporate governance in Chinese e-commerce listed companies. Chinese e-commerce listed companies listed on the Shanghai and Shenzhen stock exchanges between 2010 and 2020 are used as sample companies. With the help of fixed effects regression models and correlation matrices, this study finds that board size has a significantly active effect on executive compensation and ownership concentration is adversely correlated with executive compensation in Chinese e-commerce listed companies. Meanwhile, neither board independence nor remuneration committee meetings are significantly related to executive compensation in Chinese e-commerce listed companies. This study contributes to the understanding of the correlation between executive compensation and corporate governance and enriches the literature in this area.